Body composition assessment in male basketball players in brazilian national basketball league - Marcelo de Castro César; Arthur Paiva Neto (Universidade Federal de Santa Catarina, 2005)
This study aimed to establish the body composition profile of athletes who participated in the 2003 Men's National Basketball League. Eighty-five athletes from eight teams were measured. The data were collected between 04/24 and 05/10/2003, for the following variables: body mass, stature, body mass index, lean body mass, fat mass, skinfolds (subscapular, triceps, biceps, chest, midaxillary, suprailiac, abdominal, medial thigh and medial calf). The profile was determined by the sum of 9 skinfolds, sum of the trunk skinfolds, sum of extremity skinfolds, percent of body fat (Jackson & Pollock) and body mass index. The data showed that there was a decrease in stature from pivots to line-pivots, lines, linebackers and backfields. The pivots and line-pivots were heavier than the lines and the latter heavier than the linebackers and backfields. The pivots also had higher BMI values than lines and linebackers and no differences were found among the other groups. The pivots showed higher percent of body fat, lean body mass, fat mass, sum of 9 skinfolds, sum of the trunk skinfolds and sum of extremity skinfolds than the other groups. Once again no differences were found among the other groups. The results pointed out that stature was determinant in player's performance when analyzing by position and also that the pivots showed higher amount of body fat and total body mass than players in other positions. RESUMO Este trabalho se propôs a estabelecer o perfil da composição corporal dos atletas participantes da Liga Nacional 2003 de basquetebol masculino. Foram avaliados 85 atletas de oito equipes participantes da Liga. Os dados foram coletados entre 24/04 e 10/05/2003, sendo avaliados os seguintes itens: peso, altura, índice de massa corporal, peso da massa magra, peso de gordura, dobras cutâneas subescapular, triciptal, biciptal, peitoral, médio axilar, supra ilíaca, abdominal, coxa medial e panturrilha medial. Os seguintes parâmetros foram utilizados na determinação do perfil dos atletas: somatório de nove dobras, somatório das dobras de tronco, somatório das dobras de membros, percentual de gordura (Jackson e Pollock) e índice de massa corporal. A partir destes dados foi verificado, entre os grupos, uma redução na altura na seguinte ordem: pivôs , alas-pivôs, alas, alas-armadores e armadores. Os pivôs e alas-pivôs apresentaram-se mais pesados que os alas e estes mais pesados que os alas-armadores e armadores. Os pivôs apresentaram também maior IMC que os alas e alas-armadores. Nos demais grupos não foram encontradas diferenças. O grupo dos pivôs apresentou maiores percentual de gordura, peso da massa magra, peso de gordura, soma das nove dobras, soma das dobras de tronco e soma das dobras de membros que os demais grupos, os quais não apresentaram diferenças entre si. Os resultados evidenciam que a estatura é determinante na performance dos jogadores por posição e os pivôs apresentam maior quantidade de gordura corporal e massa corporal total que os jogadores das demais posições.